Sistem Recruitment Pegawai (Studi Kasus: Mahar Agung Organizer) - Rizkia Desi Yudiari; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mahar Agung Organizer has many parameters in selecting candidates that cause a lot of time during manual processing. Project manager's selection in February 2018 was then estimated at more than five hundred job applicants. In the August 2018 official crew selection, it was estimated that job applicants reached one thousand six hundred candidates. In addition, there was no process of classifying the types of events suitable for official crew after being accepted, causing the project manager to review the results of the interview to place the crew official in the list of events. The absence of a concise page that can display information related to official crew work performance to assess official crew performance is also one of the problems that is expected to be resolved through this research. This research will be conducted using an Object-oriented (OO) approach that will use Use Case Diagrams, Sequence Diagrams, and Class Diagrams in making systems. The development cycle uses the Prototype method by doing two iterations according to the agreement in the beginning with the stakeholders. This system will have three main features. The first feature will be implementing selection of candidates with Profile Matching. The second feature is a function for placing candidates who have been accepted into their divisions using the Naive Bayes algorithm. The third feature is displaying official crew performance in the form of dashboarding information. Validation testing using Black Box produces 100% validity. Unit testing and integration testing using White Box is in accordance with expected result.